Dampak Penerapan Program SLPTT terhadap Pendapatan Usahatani Padi di Kecamatan Telagasari Kabupaten Karawang - Fajar Firmana; Rita Nurmalina (Agrikultura, 2016)
ABSTRACTThe Impact of the Program SLPTT on the Paddy Farm Business Income in Telagasari District, Karawang RegencyOver the past five years, rice consumption level of Indonesian population is still relatively high, at an average of 136.268 kg per capita per year. Although rice production in Indonesia has increased, government still imports to meet domestic demand. One of government's efforts to solve the problem is by implementing the Field School of Integrated Crop Management (SLPTT). The purposes of this research are to describe the activity of technology on rice farming, to evaluate the implementation of SLPTT and non-SLPTT program, and to analyze the income of rice farm business from SLPTT and non-SLPTT program in Kalibuaya Village. The study was conducted with direct observation and interview to the rice farmers in Kalibuaya Village as respondents selected by cluster sampling and purposive sampling method. The differences of the technology components used in the rice farming activities were detected between farmers of the SLPTT and non-SLPTT program. Rice farm business of the SLPTT program wass more efficient than non-SLPTT program with ratios of R/C on total cost were 1.88 and 1.79, respectively.Keywords: Rice production, Rice farming activities, R/ C, SLPTTABSTRAKSelama lima tahun terakhir, tingkat konsumsi beras penduduk Indonesia masih tergolong tinggi yaitu rata-rata 136,268 kg per kapita per tahun. Meskipun saat ini produksi beras di Indonesia mengalami peningkatan, akan tetapi sampai saat ini pemerintah masih melakukan impor untuk memenuhi kebutuhan dalam negeri. Salah satu upaya pemerintah untuk mengatasi masalah ini yaitu dengan menerapkan program Sekolah Lapang Pengelolaan Tanaman Terpadu (SLPTT). Tujuan penelitian ini adalah mendeskripsikan keragaan teknologi usahatani, mengevaluasi penerapan komponen teknologi program SLPTT dan non program SLPTT, menganalisis pendapatan usahatani padi program SLPTT dan non program SLPTT. Penelitian dilakukan dengan observasi langsung dan wawancara kepada petani sebagai responden di Desa Kalibuaya melalui metode cluster sampling dan purposive sampling, Terdapat beberapa perbedaan penggunaan komponen teknologi antara petani program SLPTT dan non SLPTT ketika melakukan kegiatan usahatani padi. Usahatani padi program SLPTT lebih efisien dibandingkan dengan non program SLPTT dengan rasio R/C atas biaya total masing-masing sebesar 1,88 and 1,79.Kata Kunci: Produksi padi, Activitas usahatani padi, R/C, SLPTT